Ketimpangan Gender dan Human Security dalam Ancaman Keamanan TKW Indonesia di Arab Saudi - Felisa Marimbunna Tandi (Indo Publishing, 2026)
This research examines the relationship between gender inequality and human security in the context of Indonesian women as migrant workers in Saudi Arabia. Structural vulnerability will be emphasized in this study, as it relates not only to economic factors but also to the influence of social systems, laws, and unequal power relations. Through a feminist perspective and supported by the concept of human security, this study examines how threats to individual safety emerge and the role of the state in providing protection. This research explores the relationship between gender inequality and human security in the context of Indonesian women working as migrants in Saudi Arabia. This study emphasizes structural vulnerability due to economic factors and the impact of unequal social, legal, and power relations. This study examines how threats to individual safety emerge and the role of the state in providing protection through a feminist perspective and the concept of human security.